Postmortem Changes as Documented in Postmortem Computed Tomography Scans. Issue 1 (March 2016) - Andrews, Sam W.
The benefits and uses of postmortem computed tomography (PMCT) have been well documented in the forensic pathology and radiology literature in recent years and research into its utility continue in earnest. Opinions and policies regarding who actually interprets the PMCT scans vary between institutions, but in general, scans will be read by a forensic pathologist, a clinical radiologist, or a clinical radiologist with a special interest or training in postmortem imaging. Differences between clinical computed tomography scans and PMCT scans have been well documented and knowledge of these differences, typically those due to postmortem changes, is essential to the reader of the PMCT scan so as to minimize the risk of misinterpretation and, potentially, misdiagnoses.